Speaking Problems of EFL Students at English Education Study Program in Muhammadiyah Luwuk University - ST. Marhana Rullu; Hamia Daburan (BABASAL English Education Journal, 2020)
This research emphasized the problems of speaking ability in English among students of English Education Study Program in Muhammadiyah Luwuk University. This type of research was descriptive qualitative. In this research, the researcher used interview as instrument to find out the problems faced by the students in speaking English. From the results of the research, the researcher found the main problems faced by the students were limitations on vocabulary, errors in pronunciation, and incorrect grammar. In addition, the students also got anxiety when they speak in English and they embarrassed when they speak incorrectly, and they are still affected by their native language until they have problems in speaking English.Keywords: Speaking; Speaking Problems.